Maintenance of fuel spray nozzle in fuel component workshop MAS Aerotechnologies Sdn Bhd / Azli Abdul Manap and Hussin Hashim - Abdul Manap, Azli; Hashim, Hussin (2000)
This project is for the fulfillment of the requirement needed for final semester in Diploma In Aerospace Mechanical Engineering. The project research was done in Component Workshop, MAS Aerotechnologies Sdn Bhd (MASA). The study of Aircraft Fuel and Fuel Spray Nozzle was done in Fuel Component Workshop. The study also included the Maintenance Documentation and Process that carry out in the Shop. In this project we also learned about the Overhaul Process of the Fuel Spray Nozzle on PW 125 Engine. Lastly, we hope that the report will satisfy the requirement and also can give some information on Maintenance Aircraft Fuel Nozzle.